Acquisition of information literacy skills by studetns with disabilities: the role of the Nigerian school library media specialist (2010)
Information literacy recognizes the need for information to solve problems, develop ideas and locate appropraite information that would be used by individuals. The school library media centre has an important role of disseminating information to all students regardless of their physical abilities. This article examined the acquisition of information literacy skills by disabled students and the role of the school library media specialist in ensuring that they become information literate through the teaching of information skills that wpuld give them lifelong support in accessing information necessary for their daily living. The study also examined the objectives of information literacy and the advantages of information literacy skills. The article recommended, among others that school library media specialist should work pro-actively in partnership with special education teachers through curriculum planning and also to align the school library with educational goals as relating to information literacy skills of the disabled. Gender link is not a determinate of getting into managerial cadre in Librarianship in Nigeria. This article is of value to those interested in studying gender inequality. "